Pressureless electron beam sintering of Al2O3–Ti composite in the forevacuum pressure range. Issue 2 (15th January 2023) - Klimov, A.S.; Bakeev, I. Yu; Oks, E.M.; Zenin, A.A.
Abstract: The results of our investigations of pressureless electron beam sintering of Al2 O3 /Ti composite in the fore-vacuum range of pressure are described. A novel kind of electron source for irradiation the surface of a compacted composite with a focused electron beam at a pressure of 30 Pa was used. The effect of different electron-beam irradiation regimes and compact size on the sintered material hardness, density and porosity is described. The measured and calculated temperature variation across the sample thickness are discussed. It is shown that after the electron-beam sintering there are formed in the bulk of the sample three regions with different porosity and hardness. The microhardness in the middle of the sample reached 29 GPa. These regions are formed due to the low thermal conductivity of the alumina ceramic component of the composite. The sintering regimes that produce samples with low porosity are determined.